Long-term exposure to wildfire smoke and mortality: Heterogeneous effects by exposure metric and across subpopulations - Lara Schwarz; Timothy B. Frankland; Sara Y. Tartof; Gina S. Lee; Yuqian M. Gu; Elizabeth Rose Mayeda; David J. X. González; Tarik Benmarhnia; Joan A. Casey; Chen Chen (Proceedings of the National Academy of Sciences, 2025)
Wildfire smoke, once rare, is a hazard that populations across the globe are increasingly exposed to repeatedly. Evidence of acute health effects of wildfire particulate matter (PM 2.5 ) is growing, but less is known about long-term effects related to repeated exposures. Using a cohort of 1,250,083 Kaiser Permanente Southern California members aged ≥60, we estimated the association between all-cause mortality and 3-y exposure to five different census tract–level wildfire smoke metrics (mean daily wildfire-specific PM 2.5 , mean daily wildfire-specific PM 2.5 during the peak wildfire week, number of days with daily wildfire-specific PM 2.5 > 0 μg/m 3 , number of weeks with average wildfire-specific PM 2.5 > 5 μg/m 3 , and number of smoke waves). We applied a discrete-time approach with pooled logistic regressions, adjusting for sex, age, race and ethnicity, marital status, smoking status, requiring an interpreter, calendar year, and census tract–level poverty and population density. When comparing those highly exposed (95th percentile) to those minimally exposed (5th percentile), we found an increased odds of mortality across all five wildfire smoke metrics. Mean daily wildfire PM 2.5 was the metric most strongly associated with mortality (odds ratio: 1.07; 95% CI: 1.05, 1.09). We observed greater vulnerability to the long-term effects of smoke for individuals under age 75, or with Black or Other racial/ethnic identity, or living in a census tract with higher poverty. Identifying the most harmful long-term wildfire smoke metric and most-at-risk populations can help focus attention for developing effective adaptation strategies in a changing climate.